Gene therapy for C-26 colon cancer using heparin-polyethyleneimine nanoparticle-mediated survivin T34A - Zhang, Ling (Dove Medical Press, 2011)
BACKGROUND: Gene therapy provides a novel method for the prevention and treatment of cancer, but the clinical application of gene therapy is restricted, mainly because of the absence of an efficient and safe gene delivery system. Recently, we developed a novel nonviral gene carrier, ie, heparin-polyethyleneimine (HPEI) nanoparticles for this purpose. METHODS AND RESULTS: HPEI nanoparticles were used to deliver plasmid-expressing mouse survivin-T34A (ms-T34A) to treat C-26 carcinoma in vitro and in vivo. According to the in vitro studies, HPEI nanoparticles could efficiently transfect the pGFP report gene into C-26 cells, with a transfection efficiency of 30.5% ± 2%. Moreover, HPEI nanoparticle-mediated ms-T34A could efficiently inhibit the proliferation of C-26 cells by induction of apoptosis in vitro. Based on the in vivo studies, HPEI nanoparticles could transfect the Lac-Z report gene into C-26 cells in vivo. Intratumoral injection of HPEI nanoparticle-mediated ms-T34A significantly inhibited growth of subcutaneous C-26 carcinoma in vivo by induction of apoptosis and inhibition of angiogenesis. CONCLUSION: This research suggests that HPEI nanoparticle-mediated ms-T34A may have a promising role in C-26 colon carcinoma therapy.